Starch modifications via physical treatments and the potential in improving resistant starch content - Zailani, Mohd Alhafiizh; Kamilah, Hanisah; Husaini, Ahmad; Awang Seruji, Awang Zulfikar Rizal; Sarbini, Shahrul Razid (Wiley, 2022)
Native starches from various plant origins have limitations in their physicochemical properties. These properties influence the qualities of formulated food products, especially in appearance, texture, structure, and taste. Therefore, modification is required to improve the properties and functionalities of starch. Additionally, starch modification is able to enhance functional food properties. Functional food refers to natural or processed foods that contain bioactive compounds, which are clinically proven to promote consumer's health. These bioactive compounds have targeting mechanisms that can manage, prevent, or treat diseases. Modified starches display improvement in resistant starch (RS) content that exhibit functional food properties such as having a low glycemic index and promotes thegrowth of probiotics; Lactobacillus sp. and Bifidobacterium sp. This review discusses the modification of starch, specifically heat moisture and microwave heat treatments, in improving the RS content. Furthermore, the relationship between RS and prebiotic properties of starch is also elaborated. Factors influencing the RS content include the amylose–amylopectin ratio and retrogradation period. Meanwhile, the influence of RS content on the prebiotic properties of modified starches is linked to its resistance to digestion. However, further investigation regarding the extent to which RS can contribute prebiotic properties is also an area of interest for future/subsequent exploration.